Proses Penerimaan dan Pencatatan Kas Penjualan di PT. Arjuna Utama Kimia - Seventeen Dwi Augustya; Mochammad Isa Anshori (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to describe the process of receiving and recording cash sales at PT. Arjuna Utama Chemistry. With the Independent Learning Campus (MBKM) policy from the Ministry of Education and Culture, Trunojoyo Madura University is holding an industrial internship program that provides students with direct experience in the world of work. This report provides an overview of the stages of cash receipt and recording, as well as the importance of the reconciliation and reporting process in maintaining the accuracy and transparency of the company's finances.